The Level of Awareness and Utilization of Computer Shields among Computer users in a Nigerian Community - Ihemedu, Chidi Oliver; Omolase, Charles Oluwole (Asian Journal of Medical Sciences, 2011)
Objective: This study was designed to determine the level of awareness and extent of use of computer shields among computer users in Owo, in South-West Nigeria. Material & Methods: The subjects were selected by a simple random sampling method. Data collection was through a combination of e-mail based on-line questionnaire using the survey monkey website, and the self administered semi structured hard copy questionnaire. The information obtained from the respondents with the questionnaire included their bio-data, extent of computer use, history of ocular symptoms, awareness and utilization of computer shields. The data obtained with the study instrument was collated and analyzed using the SPSS 15.0.1 statistical software, cross tabulation of attendants results were done with chi-square test and statistical significance was set at p ≤ 0.05. Results: 108 of 124 selected subjects filled their questionnaire to acceptable level. There were a large number of respondents who were aware of the various types of computer shields (70.5%) (p-value 0.002). However, the utilization level was not commensurate as only 39.8% (N= 43) utilized any of these shields, 49.1% (N= 53) were none users while 11.1% (N= 12) did not respond (p-value 0.062). Conclusion: Majority of the respondents were aware of computer shield. However, less than half of the respondents utilized computer shields. There is need to encourage all computer users on the use of computer shields to ensure better computer working time. Key Words: Awareness; Computer shields; Nigeria DOI: 10.3126/ajms.v1i2.2826 Asian Journal of Medical Sciences 1 (2010) 49-52